Experimental study on motions of tunnel element during immersion standby stage in long wave regime. (1st August 2018) - Song, Yue; Zhang, Ningchuan; Huang, Guoxing; Sun, Zhenxiang
Abstract: The motions of a small-freeboard tunnel element are prone to strongly nonlinear wave-body interaction as a result of significant water-on-deck occurrence. To obtain a better prediction for the accurate and safe handling of a tunnel element in severe weather, 3D physical model tests were conducted under regular and irregular waves with long period to estimate the motions of three floating bodies (single tunnel element, pontoon and the tunnel-pontoons assembly) and predict possible resonance. The experimental results demonstrate that, due to the green water loadings, the non-zero mean heave of the tunnel and tunnel-pontoons assembly is significantly affected by roll resonant motion and has a similar dependence on the wave period as the roll in long wave regime. For wave period smaller than the roll period, the mean drift forces have substantial influence on the mean sway of all the three floating bodies, provoking greater offshore mooring tensions. Wave excitation at periods close to resonance of the heave, roll and pitch results in large local peaks in RAOs of the three floating bodies. Highlights: Based on the project of Hong Kong-Zhuhai-Macau Link, an experimental study was conducted. The motion of standby tunnel and tension on mooring lines were measured simultaneously under both wind wave and swell. The green water, caused by small freeboard of the tunnel system under long wave, leads to a significant non-zero mean heave. The variation of the mean heave is significantly affected by the resonant period of roll as well as the wave period. Both low-frequency and mean drift force play a key role on horizontal displacement and mooring tension of the standby tunnel.